GRAFISMOS - Realpe, Andree Julieth Villota (Revista Horizontes Literario, 2015)
Virginia Woolf, Alejandra Pizarnik, Silvia Plath, Hemingway, Tolstoi, Balzac, Faulkner, Allan Poe, Twain, sumados a Charles Baudelaire y al gran Gerard de Nerval…